HDTV : assessing an innovation at three points in time - Elias, Jaan, (SAGE knowledge. Cases., 2016)
When colour television reached the mass market, many broadcasters dreamed of another goal - to improve the television picture so that it would rival that of motion pictures. This study examines the development of HDTV at three particular points in time.